DIGITAL TECHNOLOGY AND PRIVACY REGULATIONS IN FINANCIAL ACCOUNTING: AN EMPIRICAL STUDY USING INSTITUTIONAL THEORY AND TAM - Raspini Raspini; Agus Wibowo (Jurnal Akuntansi dan Bisnis, 2026)
The rapid advancement of digital technology, coupled with the tightening of data privacy regulations, has significantly impacted financial accounting practices. However, empirical studies examining how these regulations influence accounting processes remain limited. The novelty of this research lies in its integrative approach, combining Institutional Theory and the Technology Acceptance Model (TAM) to analyze the role of digital technology and privacy regulations in transforming financial accounting. By employing a mixed-methods research design, this study integrates quantitative analysis of financial reports and surveys with qualitative interviews and case studies. The quantutative component measures the impact of privacy regulations on financial reporting and compliance, while the qualitative analysis explores the challenges faced by accountants and auditors in implementing these regulations, as well as the adaptive strategies they employ. The integration of Institutional Theory helpes explain external pressures, such as regulatory and professional demands, while TAM provides insight into the internal acceptance of digital tools by accounting professionals. This study contributes to bridging the empirical gap in accounting research by offering a comprehensive understanding of organizational responses to technological innovation and regulatory environment in the digital era.